(untitled) (Research, Society and Development, 2023)
Objective: To denote the performance of health professionals in combating Covid-19 inserted in the drive-thru model for mass immunization of the population, demonstrating the result of this action in the city. Methodology: Descriptive study, of the report type of experience of the professionals of the Residency Program in Collective Health in the vaccination against Covid-19, in the drive-thru model in the Centro de Eventos of Ponta Grossa, Paraná. Results: The vaccines used in the immunization against Covid-19 in the municipality, correspond to 4 different laboratories, distributed according to population demand, following the guidelines of each manufacturer, being applied a total of 802,779 doses. The site of choice for vaccination was based on analyses that would facilitate the logistics of the immunization process, avoiding compromising the flow of cars in the city and ensuring the safety of workers. The health professionals worked in the screening stage and in the application of immunizers, with the support of municipal professionals and interns. The implementation of online scheduling and the use of technology also contributed to the organization and agility of the immunization process. Conclusion: This model enabled agility in the application of vaccines, providing comfort to patients, especially those with limitations, and also showed the importance of collective and multiprofessional work.